Super-twisting sliding mode based nonlinear control for planar dual arm robots - Tung Lam Nguyen; Huu Tinh Vu (Institute of Advanced Engineering and Science, 2020)
In this paper, a super-twisting algorithm sliding mode controller is proposed for a planar dual arm robot. The control strategy for the manipulator system can effectively counteract chattering phenomenon happened with conventional sliding mode approach. The modeling is implemented in order to provide the capability of maneuvering object in translational and rotational motions. The control is developed for a 2n-link robot and subsequently simulations is carried out for a 4-link system. Comparative numerical study shows that the designed controller performance with good tracking ability and smaller chattering compared with basic sliding mode controller.